Assessing a b-learning teaching approach and students’ learning preferences in higher education - Cardoso, T; Pestana, F.; Aragão e Pina, J. (EDULEARN19 Proceedings, 2019)
Distance learning has been gaining ground in higher education institutions, particularly in the context of blended learning, forcing institutions and teachers to confront new challenges in the teaching / learning process [1] [2] [3] [4]. This trend has been increasing in the world [5] [6], namely in the United States [1] [7] and in Europe [8] [9] [6] [10]. Blended learning, or simply b-learning, has been associated with the reduction of costs and efficiency [11] [3]. According to several authors, it enables to combine face-to-face and online distance modalities (elearning or mlearning), so it is said to be the better of both worlds [12] [13] [14]. It also allows to enhance greater space-time flexibility, and when properly implemented allows the acquisition of meaningful learning, centered on student autonomy, which, among other aspects, takes into account different learning styles/preferences. Therefore, blended-learning can inspire course curriculum design, including updating former face-to-face pedagogical offers in order to meet the blended or hybrid principles and delivery. Bearing in mind this teaching / learning specific scenario, we developed two surveys to assess such a new teaching approach and the students' preferences, in two different moments - at the beginning and at the end of a higher education unit course. Hence, in this text, we will present those surveys, as well as their theoretical and methodological framework. Both surveys have already been validated and tested, and preliminary data analysis is being developed. We expect this pedagogical approach can contribute to sustain the assessment of teaching practices towards students' learning preferences, and the choice of adequate technologies to fit those preferences. Ultimately, we expect the results can shed light for further research, so as to improve the development of blended-learning course curriculum design in higher education.